LEADERSHIP ABILITIES AS PREDICTORS OF SUCCESSFUL PROFESSIONAL ACTIVITY OF THE MODERN UNIVERSITY TEACHER - Olga Solovyova; Victor Ozerov; Alexander Maslennikov (Вестник Северо-Кавказского федерального университета)
The article describes various factors that determine the success of teaching in modern educational conditions. The article reveals the concept of ((leadership skills» in the context of professional-personal model of a successful university teacher. It is shown that leadership skills are predictors of successful professional activity of a university teacher, providing not only specific achievements, but also creating psychological stability and resilience in the situation of professional pedagogical activity.